Pendidikan Karakterpada Anak Usia Dini: Sudut Pandang Psikologi Perkembangan Anak - Fatmawati Fatmawati (Sekolah Tinggi Agama Islam al-Amin, Gersik, Kediri, Lombok Barat, NTB, 2020)
Developmental psychologists assume that the changes that occur are assumed to achieve something better and produce behaviors that are adaptive, more organized, more effective, and more complex. From various literature studies, physical development is related to changes in bodily functions, intellectual development includes cognitive development and language related to the thinking process. Meanwhile, emotional development refers to developments related to basic human emotions that are felt and expressed, while socio-moral development is related to various changes in children's ways when dealing with the social environment and the various rules and manners that exist. From the above explanation, the authors propose formulation of the following problems: a) What are the important issues in developing children? b) What is the role of education in shaping children's character? c) Who are the sources of children's character formation?Character is a container of various psychological characteristics that guide children to be able to adapt to the variations in the environment they are facing. In other words, the character will